Legal Analysis of the Protection of the Rights and Obligations of Female Workers in the Manufacturing Industry from the Perspective of Labor Law Based on Law No. 6 of 2023 Concerning Job Creation - Dwi Atmoko; Sugeng Sugeng (JURNAL AKTA, 2026)
Currently, the development of the manufacturing industry in Indonesia is experiencing quite rapid growth. Investors are entering Indonesia, many of them establishing companies that certainly require a lot of workers, including female workers. As is known, the emergence of the Employment Law contained in Law No. 6 of 2023 concerning Job Creation provides a "breath of fresh air" for workers, especially female workers, who of course have rights and obligations in carrying out their work, most of which are in the manufacturing industry. In this study, a normative juridical research method is used, where in this study an approach is taken through laws and regulations, theories, certainty theories and other legal materials that support the writing of this research. In this study, after further observation and analysis, there are several things related to the rights and obligations of workers, especially women regulated in Law No. 6 of 2023, of which there are profitable sides, namely related to maternity and birth leave as well as working hours and transportation, but on the other hand, the less profitable side is the flexibility of a certain time work agreement which can be extended continuously by the company, which in the future is feared giving rise to conflict which ultimately leads to termination of employment. In addition, there is a need for supervision by local Manpower Office officials to periodically evaluate and monitor the company, so that it can be ensured that the company is implementing its regulations properly and correctly so as not to cause conflict in the employment sector.